Firm Exports, Foreign Ownership, and the Global Financial Crisis - Peter Eppinger; Marcel Smolka (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The exceptional export performance of foreign-owned firms is a well-established stylized fact, but the underlying mechanism is not yet fully understood. In this paper, we provide theory and empirical evidence demonstrating that this fact can be explained by ownership differences in access to finance. We develop a theoretical model of international trade featuring firm heterogeneity and credit market frictions in which foreign-owned firms can access foreign capital markets via their multinational parents. The model predicts a financial advantage of foreign ownership for exporting that gains importance as credit conditions deteriorate. To empirically identify this effect, we estimate a triple differences model using rich micro data from Spain that exploits the global financial crisis as an exogenous shock to credit supply. We find that foreign ownership significantly stabilized firm exports when liquidity dried out in the crisis, in particular among small and financially vulnerable firms.
Keywords: F10; F14; F23; G01; G32; 330; firm exports; foreign ownership; multinational firms; financial frictions; financial crisis